Indicators in Higher Education for Bachelor of Public Universities in the Kingdom of Saudi Arabia - A comparative study between the parity index for each university and for each administrative region for the years 2016, 2017, 2018. - El- Siddeg, Halla El- Ziber (Journal of Economic, Administrative and Legal Sciences, 2020)
The present study aims: sought to research in the indicators of gender parity in higher education for Bachelor degree of public universities in Saudi Arabia. Its importance was that it seeks to provide a database of indicators of sustainable development in general and the equivalence index in particular, and the localization of sustainable development goals within the vision of the Kingdom 2030, in addition to know the differences between universities in terms of the equivalence index. The researcher used a descriptive analytical method. The research came out with several results, most notably: The gender parity index in most higher education in public universities in the baccalaureate stage according to statistics, was in favor of females in the years: 2016، 2017، 2018. The inequality index over the three years 2016، 2017، 2018 was favored by females in the north, and south of Saudi Arabia. It also made a number of recommendations, including: Increase the number of studies and researches concerned with higher education in public universities in the Kingdom of Saudi Arabia (undergraduate).